COPYRIGHT INFRINGEMENT IN VIRTUAL CONCERTS - R. Gratikana Ningrat; Henry Soelistyo Budi (Faculty of Law, Universitas Pelita Harapan | Lippo Village, Tangerang 15811 - Indonesia, 2022)
So far, technological advances have encouraged the formation of new patterns of life, with creative and innovative ideas, concepts, and thoughts. In the music industry, for example, various digital media and virtual concert venues have developed as a form of breakthrough in dealing with various obstacles due to the Covid-19 pandemic. Virtual concerts are interesting to study because they allow the Author to announce his creation for the first time as the basis for the existence of a Copyright and perform musical performances, including choreographed works. However, on the other hand, it eases other people to fix or record the virtual concert without permission, then distribute it for commercial purposes. In this regard, normatively, the Copyright Law has norms to prohibit such illegal acts. Having said this, this research is addressed to examine how the regulation and implementation of the Copyright Law is for the choreographic works performed in Virtual Music Concerts. The type of research utilizes normative juridical with empirical juridical support. In the perspective of legal certainty, the results of the study conclude that choreographic works do not include works that are managed by the National Collective Management Organization’s potential royalty revenue, as is the case with song and/or musical creations. Therefore, to achieve legal certainty in copyright protection, the authority of the National Collective Management Organization needs to be broadened to include the management of royalties for the use of choreographic works for commercial purposes which has implications for the revision of the Copyright Law and Government Regulation No. 56/2021.